(untitled) (Asian Journal of Social Science Studies, 2026)
Introduction: Globally, at least 1 in 3 women has experienced some form of gender based abuse during their life time. Domestic violence occurs across the world in various cultures and affect people across society, irrespective of economic status. Aim: The aim of this study is to assess the prevalence, patterns and determinants of domestic violence among women in households in communities in Imo State. Methodology: This was a cross-sectional descriptive study carried out among 600 women living in households in Imo State. The multistage sampling technique was used to select the study participants and data was collected using a pretested, interviewer administered and semi-structured questionnaire. The data was analyzed using a computer software (EPI INFO version 7.1.3, CDC, USA), and was presented on frequency tables and percentages. Associations between variables was done using Chi-square and logistic regression where necessary. P value of ≤ 0.05 was considered statistically significant. Result: The mean age of women studied was 31.5±1.4 years. The prevalence of life time and current experience of domestic violence among the women were 72.8% and 42.6% respectively with physical (49.2%) and sexual (31.2%) abuse being the commonest types experienced. Factors found to be associated with current abuse were; age of women, (p=0.040),religious set attended, (p=0.004), occupational status of women, (p=0), marital status, (p=0.028), occupational status of partner, (p=0), place of residence, (p=0), house hold size,(p<0.0001), monthly income of women, (p<0.0001), persons lived with, (p=0.002) and level of knowledge about domestic abuse, (p=0). Conclusion: The prevalence of domestic violence among women in this study was high. Thus, there is need for government at all levels and concerned agencies to do everything within their powers to curb this menace as this will help to improve the lives of our women.